Islamic Financing Effects on Small Medium Enterprises Competitiveness - Adedeji Saidi Adelekan (Journal of Islamic Economic and Business Research, 2021)
Islamic financing has been identified as an alternative to conventional financial services. However, the extent to which the Islamic financing model could drive small and medium enterprises' (SMEs) competitiveness has been a significant concern in the existing literature. Hence, this study investigates the impact of Islamic financing on SMEs' competitiveness. Adopting the survey research design, the study investigated 400 SME owners/managers in the Southern part of Nigeria. The study employed the ordinary least square regression in the analysis of data. The result establishes that Islamic finance is a significant driver of SMEs' competitiveness. The results specifically reveal that Islamic finance is critical in driving product price, customer experience, and quality of products. The practical implication of Islamic finance may reduce its operational cost since it comes at a no-interest rate while giving room for more innovative prices and customer-centric products at competitive prices. SMEs are to leverage on the opportunities provided by Islamic finance for them to adopt sustainable business practices